Anaerobic Treatment of Semiconductor Industry Wastewater and Biomass Acclimation - Bruno P. Escobar; Ana Rita N. Santos; Flavio G. C. S. Silva; Maria Helena G. A. G. Nadais (Chemical Engineering Transactions)
This work investigated the feasibility of an anaerobic biomass from a municipal wastewater treatment plant (MWTP) to acclimate to an effluent from a semiconductor industry for treating it over a 132 days period in semi-continuous assays. The study consisted of four phases: the Stimulation period, where the inoculum was fed with sucrose; the Acclimation period, involving a continuous increase in effluent concentration; Stabilization 1, with feeding exclusively from effluent; and Stabilization 2, where a mixture of effluents and simulated wastewater (SW) was introduced. Methanisation and chemical oxygen demand removal efficiency were on average 59% and 79% respectively. Average methane production was 0.1 mL of CH4 per mg of COD. The continuous production of methane, total volatile acids consumption, no accumulation of organic compounds and decrease in alkalinity confirmed a stable operation of the anaerobic system. An overall lower efficiency in methane production in comparison to other studies may indicate other reactions for organic degradation besides methanogenesis, as also be explained by the complex composition of the wastewater (WW) that might have caused inhibition alongside accumulation of degradation intermediates. Therefore, it is important to consider pre- and post-treatments in future studies. Results presented indicate that anaerobic inocula collect from a MWTP can acclimate and effectively treat WW from the semiconductor industry.